2016
DOI: 10.1007/s12678-016-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Deposition of Iridium onto Nickel Substrates for the Oxygen Evolution Reaction

Abstract: Spontaneous deposition of Ir onto Ni substrates was investigated as a method to produce electrocatalytic layers for the oxygen evolution reaction in 30% KOH solution. UV/Vis spectroscopy, cyclic voltammetry and other electrochemical methods are used to investigate the deposition process and the activity of the electrocatalytic coating towards the oxygen evolution reaction. From three solutions (IrCl 3 +HCl, H 2 IrCl 6 +HCl, and H 2 IrCl 6 ), H 2 IrCl 6 is shown to give the most active and stable coating, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…According When Ir was spontaneously deposited on Ni electrode from such solutions, it was shown that iridium deposits consisted of adsorbed Ir complexes, which became at least partly reduced up to metallic Ir, while Ni became oxidized. 23,24 It will be shown below that when the Au(111) electrode is immersed into the similar (1 mM IrCl 3 • xH 2 O + 0.5 M H 2 SO 4 ) depositing solution, its oxidation state does not change, but remains metallic. Therefore, gold is not a source of electrons for the reduction of Ir complexes like in the case of Ni in Refs.…”
Section: Spontaneous Deposition Of Ir On Thementioning
confidence: 99%
See 1 more Smart Citation
“…According When Ir was spontaneously deposited on Ni electrode from such solutions, it was shown that iridium deposits consisted of adsorbed Ir complexes, which became at least partly reduced up to metallic Ir, while Ni became oxidized. 23,24 It will be shown below that when the Au(111) electrode is immersed into the similar (1 mM IrCl 3 • xH 2 O + 0.5 M H 2 SO 4 ) depositing solution, its oxidation state does not change, but remains metallic. Therefore, gold is not a source of electrons for the reduction of Ir complexes like in the case of Ni in Refs.…”
Section: Spontaneous Deposition Of Ir On Thementioning
confidence: 99%
“…Depending on the composition of Ir deposit, in some cases rather featureless cyclic voltammograms (CV) of Ir-modified Ni electrode in the potential region prior to hydrogen evolution are obtained. 22,23 In contrast to this, it was shown that during spontaneous deposition of Ir on Ni from the solution containing IrCl 3 . xH 2 O salt dissolved in HCl, Ni is oxidized to Ni 2+ , while Ir z+ is reduced to metal, 24 which is confirmed by the appearance of Hupd region on CVs characteristic of bare Ir. 25 In this work, spontaneous deposition of Ir on the Au(111) surface was performed using ( (3-n) , where n is 3, 4, 5 and 6, and of Ir(IV) [Ir(H 2 0) 6-n Cl n ] (4-n) , where n is 3, 4, 5 and 6, respectively.…”
mentioning
confidence: 92%
“…This was achieved through immersion of the Ni DHBT electrode in a 0.001 M K 2 IrCl 6 + 0.01 M HCl solution for different periods. The mechanisms responsible for the spontaneous deposition of Ir on an Ni substrate were previously studied. , In an acidic electrolyte, the dissolution of metallic Ni occurs according to eqs and . Metallic Ir deposition occurs according to eq . 2 normalH + + Ni normalH 2 + Ni 2 + false[ Ir Cl 6 false] 2 + 2 Ni Ir + 2 Ni 2 + + 6 Cl …”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical measurements were conducted on four types of Ni foam-based catalyst (ca. 1.1 × 1.1 cm samples), namely: a) As-received Ni foam (acetone wash/ultrasonication 900 s at 298 K + air drying), b) Etched Ni foam (acetone wash/ultrasonication 900 s at 298 K + air drying followed by 2 M HCl acid etching 900 s at 333 K + ultra-pure water rinsing + air drying), c) Etched, Ir-modified nickel foam by spontaneous [18][19][20] deposition upon ultrasonication (0.1 M HCl + 1 × 10 −3 M IrCl 3 (Sigma Aldrich, pure p.a. ), 298 K at 30 s and 300 s), and d) Etched, Ir-modified nickel foam by electrodeposition [21] upon ultrasonication (0.…”
Section: Chemicals Solutions Electrochemical Cell and Electrodesmentioning
confidence: 99%